De-fragmenting Africa : Deepening Regional Trade Integration in Goods and Services - World Bank (Washington, DC, 2013)
This book is the result of an extensive agenda of analytical work on regional trade integration in Africa involving staff from various units of the Africa region of the World Bank. The aim of this volume is to provide the main messages from this work to a wide audience the private sector, civil society, key ministries, relevant agencies that is necessary to provide the consensus and broad base for successful implementation of reforms. Africa is not achieving its potential in regional trade. The contributions to this volume highlight the enormous scope for increased cross-border trade in Africa and the reasons why such opportunities are not being exploited. The main objective of this introductory chapter is to draw attention to the key reason why Africa's potential for regional trade remains unexploited: the high transaction costs that face those who trade across borders in Africa. The contributions to the volume discuss a wide range of policy related barriers that drive up costs and limit trade. The chapter starts with a review of recent export performance in Africa, noting the strong growth rates in many countries. However, the impact of such growth on employment and poverty has been much muted and important challenges remain, especially with regard to greater diversification of exports, and it is here that effective regional integration that reduces transaction costs can play a key role. The paper then discusses the key barriers that raise costs for traders and continue to fragment the African market. Finally, the paper ends with some specific recommendations for action that policy makers can take at the regional level to support integrated markets in Africa and discusses how the World Bank and other donors can support those wishing to implement the necessary reforms.